2015
DOI: 10.1097/fjc.0000000000000204
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics-based Warfarin Dosing Algorithm Decreases Time to Stable Anticoagulation and the Risk of Major Hemorrhage

Abstract: Warfarin is yet the most widely used oral anticoagulant for thromboembolic diseases, despite the recently emerged novel anticoagulants. However, difficulty in maintaining stable dose within the therapeutic range and subsequent serious adverse effects markedly limited its use in clinical practice. Pharmacogenetics-based warfarin dosing algorithm is a recently emerged strategy to predict the initial and maintaining dose of warfarin. However, whether this algorithm is superior over conventional clinically guided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
4
9
0
1
Order By: Relevance
“…We also meta‐analysed other endpoints about adverse events, including thromboembolism and all‐cause mortality. However, our results did not demonstrate superiority of reduced risks of these adverse events in GD group as compared with CD group, which were in consistent with previous meta‐analyses …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We also meta‐analysed other endpoints about adverse events, including thromboembolism and all‐cause mortality. However, our results did not demonstrate superiority of reduced risks of these adverse events in GD group as compared with CD group, which were in consistent with previous meta‐analyses …”
Section: Discussionsupporting
confidence: 92%
“…Results demonstrated that GD algorithm significantly shortened time to first therapeutic INR and time to reach stable therapeutic dose, and reduced the risk of warfarin‐related major bleedings. GD algorithm presented similar PTTR at ≤1 month and higher PTTR at >1 month follow‐up compared to CD method, which is in accordance with the finding of previous meta‐analyses . There was no significant difference in the incidence of patients achieving stable dose between GD and CD groups at ≤1 month follow‐up, but more patients in the GD group achieving stable dose at >1 month follow‐up.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations